Territory and pandemic: the deepening of inequality and resistance in the set of favela da Mare (RJ) (PerCursos, 2022)
This article addresses the right to the city and the worsening living conditions of workers residing in slums due to the pandemic of the new Coronavirus and the intensification of the regression of social rights in the last period. Based on the projects and the experience of Redes da Maré, a civil society organization, and on a literature review that considers the slum as an expression of unequal and combined development of capitalism, the article aims to give visibility to the impacts of social setbacks in the lives of slum residents and also to the expressions of collective resistance in this territory. The campaign "Maré says NO to Coronavirus" and the construction of ADPF 635 (known as the ADPF of the slums) are both responses to the immediate demands of the most impoverished residents of the Maré slums and collective resistance. Both were analyzed based on insertion in the territory and professional practice and research. This paper uses a methodology that considers classical authors as a theoretical reference for the treatment of the urban question and the right to the city. It also uses empirical research and experience in projects developed in the Maré slums as a whole, based on the method of action research. This approach demonstrated the precarious living conditions of the residents of this territory and the impact of ADPF in reducing armed violence by the state. Thus, the analysis developed seeks to make explicit the need for a qualified intervention by the State and the resistance through collective organization in the territory.
Keywords: favela; Maré; right to the city; pandemic; ADPF 635